2002
DOI: 10.1046/j.1468-1331.2002.00341.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological deficits in essential tremor: an expression of cerebello‐thalamo‐cortical pathophysiology?

Abstract: Few studies have been published regarding the neuropsychological characteristics of patients with essential tremor (ET), but preliminary findings suggest that mild attentional and executive dysfunction accompany the disorder. A consecutive series of 101 patients with ET referred for thalamotomy and/or thalamic deep brain stimulation candidacy work-up also underwent neuropsychological evaluation. Average neuropsychological test scores were calculated, along with the proportions of subjects whose scores fell wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
174
1
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(189 citation statements)
references
References 43 publications
6
174
1
8
Order By: Relevance
“…20 A variety of non-motor features, including cognitive and psychiatric, are now appreciated and undergoing further scientific scrutiny in case-control studies. While mild problems in cognition in excess of aging have been reported in many case-control studies, [6][7][8] there have been few attempts to examine whether these cognitive problems are more considerable.…”
Section: Cross-sectional Analyses (Baseline Data)mentioning
confidence: 99%
See 1 more Smart Citation
“…20 A variety of non-motor features, including cognitive and psychiatric, are now appreciated and undergoing further scientific scrutiny in case-control studies. While mild problems in cognition in excess of aging have been reported in many case-control studies, [6][7][8] there have been few attempts to examine whether these cognitive problems are more considerable.…”
Section: Cross-sectional Analyses (Baseline Data)mentioning
confidence: 99%
“…[3][4][5] In a growing number of studies, mild cognitive problems are being observed in ET cases. [6][7][8] Furthermore, an association between ET and dementia was reported in a recent population-based study in central Spain. 9,10 This novel association has yet to be verified in other populations.…”
mentioning
confidence: 99%
“…Mild cognitive deficits have been reported to occur in patients with essential tremor (ET) in many independent studies, [1][2][3][4][5][6][7][8] including a population-based study of largely treatment-naive ET patients (Neurological Disorders in Central Spain [NEDICES] study). 8 These studies suggest that a frontosubcortical-type dysfunction occurs in some patients with ET.…”
mentioning
confidence: 99%
“…Studies on this subject showed cognitive impairment with affected visuospatial abilities, verbal memory, executive functions, verbal fluency, naming and working memory in ET (12,33,34,35,36). Moreover, in a limited number of studies conducted with young patients, this condition has been proved to be present even at early stages (6,13).…”
Section: Discussionmentioning
confidence: 86%
“…In several studies, findings suggesting cerebral-thalamocortical tract dysfunction were found in patients with ET. Mild cognitive impairment characterized by impairment of visuospatial functions, verbal memory, and executive functions has been shown in young patients (8,9,10,11,12,13).…”
Section: Introductionmentioning
confidence: 99%